Comercialización de los frutos de sandía (Citrullus lanatus, L.) en la Costa Ecuatoriana - Pacherre Soria, Lady Geomara (2022)
The watermelon (Citrullus lanatus L.) is a cucurbit plant, whose fruit is cultivated and widely accepted in its commercialization, at the national level. The production of this fruit in Ecuador is relevant for the agricultural sector due to its great demand for fresh consumption, to prepare jams, confectionery and as a dessert. It is one of the most cultivated vegetable items in the provinces: Manabí 20%, Guayas 20%, Santa Elena 25% and other coastal provinces 15%; These provinces stand out for their high fruit productivity. The watermelon marketing systems are dynamic and complex, within them are the distribution and marketing channels, which start from the harvest of the fruits and continue with the collection, distribution and sale processes. There are two types of marketing channels, direct channels, in which there are no intermediaries because the producer contacts the final consumer directly, and indirect channels, known for having several intermediaries: suppliers, wholesalers, and retailers between the producer and the consumer. final consumer